Simultaneous fat saturation and magnetization transfer contrast imaging with steady‐state incoherent sequences. Issue 3 (22nd September 2014) - Zhao, Feng; Nielsen, Jon‐Fredrik; Swanson, Scott D.; Fessler, Jeffrey A.; Noll, Douglas C.
<x xml:space="preserve">Abstract</x> Purpose This work combines an n‐dimensional fat sat(uration) radiofrequency (RF) pulse with steady‐state incoherent (SSI) pulse sequences, e.g., spoiled gradient‐echo sequence, to simultaneously produce B0 insensitive fat suppression and magnetization transfer (MT) contrast. This pulse is then referred to as "fat sat and MT contrast pulse." Theory We discuss the features of the fat sat and MT contrast pulse and the MT sensitivities of the SSI sequences when combining with fat sat. Moreover, we also introduce an adapted RF spoiling scheme for SSI sequences with fat sat. Methods: Simulations and phantom experiments were conducted to demonstrate the adapted RF spoiling. Fat suppression and MT effects are shown in 3T phantom experiments and in vivo experiments, including brain imaging, cartilage imaging, and angiography. Results To ensure that the sequence reaches steady state, the adapted RF spoiling is required for fat sat SSI sequences. Fat sat and MT contrast pulse works robustly with field inhomogeneity and also produces MT contrasts. Conclusion SSI sequences with fat sat and MT contrast pulse and adapted RF spoiling can robustly produce fat suppressed and MT contrast images in the presence of field inhomogeneity. Magn Reson Med 74:739–746, 2015. © 2014 Wiley Periodicals, Inc.